Tinjauan Yuridis Mengenai Sanksi Terhadap Pelaku Pemasungan Orang Dengan Gangguan Jiwa (ODGJ) - Maria Fatmawati F Taimenas; Simplexius Asa; A. Resopijani (Lembaga Pengembangan Kinerja Dosen, 2024)
Confinement still often occurs until now, especially to people with mental disorders (ODGJ), but ODGJ have the same rights as normal people in general. Some of their rights are the right to be free from torture or cruel treatment, free from exploitation and free from violence. Therefore, the act of shackling is not in accordance with our positive law. The main problems of this research are: (1) How is the juridical review of sanctions against perpetrators of shackling people with mental disorders (ODGJ)? (2) How is the ideal arrangement related to legal protection of victims of shackling people with mental disorders (ODGJ)? This research is a normative research using library research techniques and the results of this research are analyzed qualitatively.This research found several things: (1) The juridical review of the provisions of criminal sanctions for perpetrators of shackling people with mental disorders (ODGJ) has not been regulated in detail in Law Number 18/2014 on Mental Health. However, it is related to Article 333 of the Criminal Code on Deprivation of Independence, where individuals who act to confine or perpetrators of shackling can be subject to criminal sanctions in the form of 8 years imprisonment with the element of intentionally depriving someone of their freedom or acting unlawfully, a maximum of 9 years imprisonment if the action causes serious injury, and 12 years imprisonment if the victim dies. (2) The ideal arrangement related to the legal protection of victims of ODGJ confinement has been regulated in Law Number 18 Year 2014 on Mental Health which ensures that everyone has a high quality of life, mental health, free from stress, and other conditions that exacerbate mental problems. In Article 4 paragraph 1 of the Mental Health Law, legal protection of ODGJ as victims of confinement in stocks is carried out through several actions, namely: promotive, preventive, curative and rehabilitative.